Competence in Delivering Cognitive Processing Therapy and the Therapeutic Alliance Both Predict PTSD Symptom Outcomes. Issue 5 (September 2022) - Keefe, John R.; Hernandez, Samantha; Johanek, Camila; Landy, Meredith S.H.; Sijercic, Iris; Shnaider, Philippe; Wagner, Anne C.; Lane, Jeanine E.M.; Monson, Candice M.; Stirman, Shannon Wiltsey
Highlights: More CPT competent delivery was associated with lower next-session PTSD symptoms. Stronger observer-rated alliance was associated with lower PTSD symptoms. CPT competence was more predictive of outcomes when alliance was also strong. Training in competence and alliance formation in CPT may improve outcomes. Abstract: Cognitive Processing Therapy (CPT) is efficacious in treating PTSD, but there remains a need to improve outcomes for individuals who do not fully respond to treatment. Differences between patient-therapist dyads in the fidelity (i.e., adherence and competence) of CPT delivery and the quality of the therapeutic relationship may partly explain differential levels of symptom improvement. Sessions were sampled from a randomized trial comparing different consultation conditions in training therapists new to CPT. Among 69 patients, one session from Sessions 1–3 and one session from Sessions 4–7 were reliably rated for adherence and competence using the CPT Therapist Adherence and Competence Scale, and for therapeutic alliance using the Working Alliance Inventory-Observer scale. Mixed models, including detrending using a fixed effect of session, predicted self-reported Posttraumatic Stress Disorder Checklist (PCL-IV) scores in one session using process scores from the previous session. The statistical interaction between fidelity and alliance scores to predict outcome was also examined. Alliance had significant, positive correlations ( r s = 0.18–0.21) with same-session adherence and competence. Higher competence scores and higher therapeutic alliance scores in one session were independently associated with lower PCL-IV scores in the subsequent session. Adherence scores, which tended to be very high with relatively less variability, did not significantly relate to subsequent-session PCL-IV scores. Competence significantly interacted with alliance, such that sessions high in both competence and alliance predicted especially lower subsequent-session PCL-IV scores. A strong therapeutic alliance may have a synergistic, salutary effect with the competent delivery of CPT.